Factors Affecting the Length of Stay for Covid-19 Sufferers with Cormobid Hypertension - Rizqa Wahdini; Yulian Wiji Utami; Laily Yuliatun (Universitas STRADA Indonesia, 2025)
Background: Cormobid, one of the aggravating factors for COVID-19 sufferers, is hypertension. Therefore, cormobid COVID-19 sufferers can have a longer length of stay. Purpose: Thus, the researcher did a study at Soedarso Hospital in Pontianak City to find out what makes COVID-19 sufferers with hypertension cormobid stay in the hospital longer. Methods: The study used a retrospective design with a total sampling method of 204 data (15 March 2021 - 30 April 2022). Data analysis using Spearman test and ETA Correlation. Results: The Spearman test showed that there was a relationship between age (P-value 0.000, r 0.255), leukocytes (P-value 0.000, r=0.513), symptoms of COVID-19 (P-value 0.000, r=0.592), cormobid (P-value 0.002, r= 0.300) with length of hospitalization. The ETA test showed a relationship between sex (F table > F result, 3.89 > 8.14) and length of stay. Symptoms of covid-19 are the most related to the standard coefficient of beta 2,559. Conclusion: Factors affecting the length of stay for Covid-19 sufferers are age, gender, leukocytes, symptoms, and cormobid. However, the dominant factor for Covid-19 sufferers is the symptoms of Covid-19.